HEV Occurrence in Waste and Drinking Water Treatment Plants - Cuevas-Ferrando, Enric; Randazzo, Walter; Pérez-Cataluña, Alba; Sánchez, Gloria (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV), particularly zoonotic genotype 3, is present in environmental waters worldwide, especially in industrialized countries. Thus, monitoring the presence of HEV in wastewater treatment plants (WWTPs) is an emerging topic due to the importance of reusing water on a global level. Given the limited data, this study aimed to monitor the occurrence of HEV in influent and effluent water in waste- and drinking- water treatment plants (WWTPs and DWTPs). To this end, different procedures to concentrate HEV in influent and effluent water from WWTPs and DWTPs were initially evaluated. The evaluated procedures resulted in average HEV recoveries of 15.2, 19.9, and 16.9% in influent, effluent, and drinking water samples, respectively, with detection limits ranging from 103 to 104 international units (IU)/L. Then, a one-year pilot study was performed to evaluate the performance of the selected concentration method coupled with three RT-qPCR assays in influent and effluent water samples from four different WWTPs. HEV prevalence in influent water varied based on both the RT-qPCR assay and WWTP, while HEV was not detected in effluent water samples. In addition, HEV prevalence using only RT-qPCR3 was evaluated in influent (n=62) and effluent samples (n=52) from four WWTPs as well as influent (n=28) and effluent (n=28) waters from two DWTPs. The present study demonstrated that HEV circulated in the Valencian region at around 30.65% with average concentrations of 6.3 x 103 IU/L. Even HEV were detected in influent wastewater samples, effluent samples from WWTPs and influent and effluent samples from DWTPs were negative. However, given that the infective dose in waterborne epidemics settings is not yet known and the low sensibility of the assay, unfortunately, no direct conclusion could be achieved on the risk assessment of environmental contamination.